Classifying the strategic capability of farmers: a segmentation framework. (1st January 2012) - McElwee, Gerard; Smith, Rob
This paper examines the capability of farmers to diversify and outlines the barriers and challenges that confront farmers. It suggests that not all farmers have a high level of 'strategic awareness capability'. The paper describes how a segmentation framework can be used to provide coherent understanding of the entrepreneurial farming business. A segmentation framework will be presented. The segmentation framework classifies farmers by their personal characteristics, the characteristics of the farm enterprise, activities and processes undertaken by the farmer and specific needs of the farm enterprise. Criteria from this framework are chosen to identify different types of entrepreneurial farmers. The resulting framework shows different types of entrepreneurial farmers reflecting the strategic orientation of the farm. Different strategic orientations in farming may require different skills. The framework provides the opportunity for individual rural ventures to determine what these skills are.